PELAKSANAAN PENDAFTARAN TANAH BERDASARKAN PUTUSAN PENGADILAN DI KOTA BUKITTINGGI - , Naldi; , Prof dr. Sudjito, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study on the implementation of land registration based on the court decision in the land office of Bukittinggi was conducted to know how the process of implementation of land registration based on court decision in Bukittinggi was performed, and to know the faced barriers in the implementation process, and how to solve them. The used study was legal study of juridical empiric or that was performed to get primary datas. The technic of data gathering was the field study related to the legal rules with literature study. It was conducted the technic of direct communication performed using the manual of unstructured interview. Data analyses was performed qualitatively and presented descriptively. This study conluded that the implementation of land registration based on court statement of Bukittinggi City was well performed, proven by all of 11 cases of land registration based on court statement were registeres. It need 7 days to perform land registration based on court statement. The implementation of land registration based on court statement in Bukittinggi City experienced some barries such as the internal condition lacked of field executors, whereas the external barries come from the courthouse that did not receive court statementon data change of land. The right owner community did not enclose the authentic certification and excuting official report. Effort made by the land office to overcome these obstacle which are internal service improverment in the land office and external efforts enchance coordination and cooperation with the land office.